Ludwig Tieck and America - Matenko, Percy (UNC Studies in the Germanic Languages and Literatures, 1954)
This study explores the question of Tieck's reception in and influence on the American literary scene before 1900, with the additional goal of shedding light on the reception in America of German Romanticism as a whole. Matenko investigates representation of Tieck in American magazines, books and text books, American translations of his work, his relationships with American authors including Poe and Hawthorne, and also includes a list of American books in Tieck's personal library.